A new method for complete quantitative interpretation of gravity data due to dipping faults - ABDELRAHMAN, El-Sayed; GOBASHY, Mohamed; ABO-EZZ, Eid; EL-ARABY, Tarek (Contributions to Geophysics and Geodesy, 2019)
We have developed a simple method to determine completely the model parameters of a buried dipping fault from gravity data (depths to the centers of the upper and lower portions of the faulted thin slab, dip angle, and amplitude coefficient). The method is based on defining the anomaly values at the origin and at four symmetrical points around the origin on the gravity anomaly profile. By defining these five pieces of information, the dip angle is determined for each value of the depth of the lower portion of the faulted thin slab by solving iteratively one nonlinear equation of the form f(α) = 0. The computed dip angles are plotted against the values of the depth representing a continuous depth-dip curve. The solution for the depth to the lower portion of the faulted thin slab (down-thrown block) and the dip angle of the buried fault is read at the common intersection of the depth-dip curves. Knowing the depth to the center of the lower portion of the faulted layer and the dip angle, the problem of determining the depth to the center of the upper portion of the faulted slab (up-thrown block) is transformed into the problem of solving iteratively a nonlinear least-squares equation, f(z) = 0. Because the depths and the dip angle are known, the amplitude coefficient, which depends on the thickness and density contrast of the thin slab, is determined using a linear least-squares equation. The method is applied to theoretical data with and without random errors. The validity of the method is tested on real gravity data from Egypt. In all cases examined, the model parameters obtained are in good agreement with the actual ones and with those given in the published literature.